G234(P) Communicating in the digital age – is it time for clear guidelines and standards? A survey of paediatric trainees. (7th April 2014) - Griffiths, B; Whitehouse, A; Prince, N; Kelly, C; Lee, HM; Round, J
Abstract : Technology has the potential to change the way doctors and patients interact improving patient care. We surveyed trainees in the London Deanery to find out how they were communicating with patients and how much training they had received in safely using new technology to share information. We examined their knowledge and use of local guidelines and the online resources available to them. 210 responses were collected. 13% of responders rated their access to the Internet at work as poor and only 15% had wireless access. Email was the most popular method of communication between professionals at work (>70%). Surface mail remained the predominant method to communicate with patients and GPs (>85%). Smart phones and social media use by trainees was commonplace (>80%) but knowledge of local guidelines on safe use of digital media was poor. There is a belief amongst trainees that new technology can be used to improve patient care. However its use challenges many principles of clinical governance. Trainees are not aware of local guidelines and are not receiving training in areas of digital media in which they are already practicing. Is it time for training standards in digital media and clearer guidance on its safe use in practice?